PREDICTION OF WELD SHAPE FACTOR IN FLUX BONDED GAS TUNGSTEN ARC WELDING FOR AISI 1020 STEEL - Harish Kumar Arya, Deepti Jaiswal, Robin Singh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
GTAW welding has a number of drawbacks, the most significant of which is the limited thickness of material that can be welded in a single pass, resulting in a decreased production rate. Thus, a new welding technique Flux Bonded Gas Tungsten Arc Welding used which limits the drawbacks of the GTAW process. In the present work, GTAW process is carried out on AISI 1020 carbon steel plates of 10mm thickness. The specimens were welded as bead on plate. Shape factor is calculated for FB-GTAW and compared with GTAW process. The microstructures and micro hardness are compared with flux and without flux at different heat inputs. The simulation of FB-GTAW process was done by NASTRAN® software. The shape factor predicted by simulation and compared with experimental shape factor at different heat inputs. Time temperature data was measured by NASTRAN® software and compared with experimental time temperature data. The shape factor decreases by FB-GTAW as compared with GTAW process. The shape factor by FB-GTAW decrease by 29.22%, 19.59% and 31.13% at 120, 140 and 160 A respectively. The Micro-hardness of more than 300HV was measured in FB-GTAW process. The Micro-hardness measured was about 200HV. The Micro-hardness measured with FB-GTAW is more than normal GTAW process. This is because due to high cooling rate the martensite formation takes place in the weld pool by FBGTAW process. While with normal GTAW process acicular ferrite and pearlite are observed in the weld metal. The FB-GTAW process shows that there was maximum error of 0.395% calculated after comparing simulation and experimental shape factor. The simulation peak temperature was 1387°C, 1300°C and 1250°C at 160 A, 140 A and 120 A respectively. Experimental results were 1350°C, 1280°C and 1235°C at above respective currents.